Anti-Helicobacter pylori, proton pump inhibitory and antioxidant properties of selected dietary/medicinal plants - Srikanta Manjegowda Belagihalli; Shylaja Mallaiah Dharmesh (International Journal of Phytomedicine, 2012)
In recent days, emphasis has been on the use of edible sources for maintenance of health. H. pylori being a main causative organism of gastric cancer and ulcers, many researchers are working in this area to overcome the problem. The plants selected for the current study have application in traditional medicine for the treatment of gastrointestinal diseases. The studies provide the scientific evidence to antiulcer potential of medicinal/dietary plants of ethnopharmacological importance and categorize them based on multi-potent antiulcer activity. In the current study anti-Helicobacter pylori, H+, K+ -ATPase inhibitory and antioxidant activity of aqueous extracts of 18 different plants were investigated. The overall antiulcer potency of selected plants was calculated as antiulcer index (AUI) based on these in vitro antiulcer activities and categorized the plants into 4 groups based on their AUI. Overall study revealed Decalepis hamiltonii as very good (AUI 81) followed by Nigella sativa, Coscinium fenestratum and Zingiber officinale as good source (AUI 61-68) for antiulcer therapy. Among the rest, 9 plants were categorized as moderate with AUI of 41 to 59 and 6 plants as poor sources with AUI of 20 to 37. Thus the results of the current study contribute towards validation of the traditional use of selected plant sources against gastrointestinal disorders.